Maybe God is like that too - Grant, Jennifer (Jennifer C.) (Sparkhouse Family, 2017)
"A young boy asks his grandma where God is in their city. Where love, joy, peace, patience, kindness, goodness, faithfulness, gentleness, and self-control are, there too is God. An ordinary day in his city opens this young boy's eyes to God's Spirit at work all around him"--